Renal Toxicity Presenting with a Fracture in an HIV Positive Adolescent - Wee, Liang Yi Justin; Thoon, Koh Cheng; Chao, Sing Ming (Journal of Pediatric Infectious Diseases, 2018)
Tenofovir is a nucleoside reverse transcriptase inhibitor commonly used to treat human immunodeficiency virus (HIV) infection in children and adolescents. We report a case of an HIV-positive adolescent male who had been treated with an antiretroviral regimen consisting of tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) and lopinavir/ritonavir (LPV/r) with a stable CD4 count. Two and a half years after starting tenofovir, he experienced a right third metatarsal shaft fracture after minor trauma, which was treated successfully with a cast. He was found to have osteopenia for which he was treated with oral phosphate and calcium/vitamin D supplementation. Three months later, he then presented with severe hypokalemia, hypophosphatemia, normal anion gap metabolic acidosis, glycosuria, and proteinuria, which were consistent with a diagnosis of acquired Fanconi's syndrome. Subsequently, his electrolyte abnormalities were corrected with replacement of potassium, phosphate, and bicarbonate (Shohl's solution). His antiretroviral regimen was switched to abacavir/lamivudine and raltegravir. Acquired Fanconi's syndrome is a known but uncommon adverse effect of treatment with tenofovir, and an awareness that it can cause osteopenia and present with fractures can alert the physician to manage and prevent this potentially serious side effect.
Keywords: tenofovir; antiretroviral therapy; acquired Fanconi's syndrome; renal proximal tubulopathy; osteopenia